FAKTOR-FAKTOR YANG MEMPENGARUHI CADANGAN KERUGIAN PENURUNAN NILAI PADA PERUSAHAAN PERBANKAN PERIODE 2018-2021 - Westin, Thomas; Salim, Susanto (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study is to find empirical evidence about the effect of non-performing loans, loan-to-deposit ratios, and capital adequacy ratios on allowance for impairment losses in banking companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The samples used in this study were 42 banking companies. The sampling technique is purposive sampling. Panel data regression analysis was used in research using the Eviews 12 statistical program. The results of this study indicate that non-performing loans have a significant positive impact on the bank's allowance for impairment losses. Based on the results of this research, the independent variables, loan-to-deposit ratio, and capital adequacy ratio are proven to have no effect on the allowance for impairment losses of the bank. The results of this study may help bank management and investors in acquiring additional information regarding the factors that affect the allowance for impairment losses on a bank, also as a reference for further research relating to factors that affect the allowance for impairment losses.